1996
DOI: 10.1016/s0035-9203(96)90099-1
|View full text |Cite
|
Sign up to set email alerts
|

A successful control programme for falciparum malaria in Xinyang, China

Abstract: This paper describes a large scale control programme for falciparum malaria in Xinyang prefecture, China, from the early 1980s to 1992. Falciparum malaria, transmitted mainly by Anopheles anthropophagus, was epidemic in Gusi, Huangchuan, Shangcheng and Huaibin counties in the prefecture in the early 1980s, 2922 cases being reported in 1984. From 1985 to 1992, DDT residual spraying and the use of bed nets impregnated with pyrethroid insecticide were introduced for 2 consecutive years in areas at higher risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The purpose of the chemoprophylaxis was explained to them (but no details on how was it conducted) and they volunteered to cooperateMacCormack 1983, Tanzania [47]Health education through meetings was delivered in tier approach to key community persons who in turn educated familiesNRAnti-malarial supplied by WHO, government committed to the Malaria control plan and health structures present at the rural site coordinated with the projectThe direction and operation of the project was taken care by the medical director of the hospital in the study area. Officials and staffs at local hospital were involvedAs many as 28% of children complained of vomiting and 56% complained of itching, and other unfavourable qualities of chloroquines were indicated for the reluctance to adhere to the medicineDapeng 1996, China [38]Before introducing the malaria control program in the community, health education through the primary health care system, by means of meetings, films, posters, and videos were conducted thus encouraging villagers to participateNRMalaria control program was carried out through the existing primary health care system already in placeAdditional experts from the provincial and central level were involved in field research, guidance and evaluation. Village doctors were responsible for the chemoprophylaxis and the clinical care of the patientsThe control program involving malaria treatment and chemoprophylaxis was less successful than the vector control.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The purpose of the chemoprophylaxis was explained to them (but no details on how was it conducted) and they volunteered to cooperateMacCormack 1983, Tanzania [47]Health education through meetings was delivered in tier approach to key community persons who in turn educated familiesNRAnti-malarial supplied by WHO, government committed to the Malaria control plan and health structures present at the rural site coordinated with the projectThe direction and operation of the project was taken care by the medical director of the hospital in the study area. Officials and staffs at local hospital were involvedAs many as 28% of children complained of vomiting and 56% complained of itching, and other unfavourable qualities of chloroquines were indicated for the reluctance to adhere to the medicineDapeng 1996, China [38]Before introducing the malaria control program in the community, health education through the primary health care system, by means of meetings, films, posters, and videos were conducted thus encouraging villagers to participateNRMalaria control program was carried out through the existing primary health care system already in placeAdditional experts from the provincial and central level were involved in field research, guidance and evaluation. Village doctors were responsible for the chemoprophylaxis and the clinical care of the patientsThe control program involving malaria treatment and chemoprophylaxis was less successful than the vector control.…”
Section: Resultsmentioning
confidence: 99%
“…Information dissemination was conducted through newspapers [32], pamphlets and news bulletins [36]. In two studies [37, 38] audio-visual materials were employed to explain the planned intervention [37]. In China, the health education was delivered through the primary health care system by the means of meetings, films, posters and videos [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies were conducted in African countries except for three studies, one each from China, India, and Thailand. Interventions were non-integrated in 23 [10,12-14,16-18,20-22,28-33,37,39-42,45,47] of the studies, while in 17 [8,9,19,23-27,34-36,43,44,46,48-50] studies intervention was integrated with routine community-based antenatal care (ANC), primary healthcare (PHC), child health days or measles, and polio campaigns. The primary comparison was between the community-based delivery strategy versus routine or facility-based care.…”
Section: Reviewmentioning
confidence: 99%
“…A recent review suggested that community-based malaria interventions, including bed net distribution, IRS, intermittent preventive therapy, and education, may be more efficient than routine or facility-based modes of implementation 11 . However, the review found only one study that assessed IRS—a study in China evaluating a program that implemented IRS while delivering insecticide-treated nets at the same time 12 . Preliminary evidence from Tanzania suggests that community-based approaches for IRS show promise both in terms of coverage and costs, but a full evaluation has not yet been completed 13 .…”
Section: Introductionmentioning
confidence: 99%